If 2x + \(\frac{1}{3x}\) + 1 = 0 find \(\sqrt[3]{{27x}^{3}\;+\;\frac{1}{{8x}^{3}}}\). |
\(\frac{3}{2}\) \(\frac{2}{3}\) 2 \(\frac{4}{3}\) |
\(\frac{3}{2}\) |
2x + \(\frac{1}{3x}\) + 1 = 0 2x + \(\frac{1}{3x}\) = -1 Multiply by \(\frac{3}{2}\) in equation, we get ⇒ 3x + \(\frac{1}{2x}\) = \(\frac{-3}{2}\) Cubing both side, ⇒ 27x3 + \(\frac{1}{{8x}^{3}}\) = \(\frac{-27}{8}\) - 3 \(\times\) \(\frac{3}{2}\) (\(\frac{-3}{2}\)) = \(\frac{-27}{8}\) + \(\frac{27}{4}\) = \(\frac{-27+54}{8}\) = \(\frac{27}{8}\) Now, \(\sqrt[3]{{27x}^{3}+\frac{1}{{8x}^{3}}}\) = \(\sqrt[3]\frac{27}{8}\) = \(\frac{3}{2}\) |